STRATEGIC ASPECTS OF ENERGY SECURITY MANAGEMENT OF INDUSTRIAL ENTERPRISES UNDER THE CONDITIONS OF CHANGING EXTERNAL ENVIRONMENT - HORAL, Liliana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study is devoted to strategic planning and management of energy security of industrial enterprises in the conditions of dynamic changes in global energy markets and modern challenges. The relevance of the topic is due to the critical importance of energy security for ensuring the stability of production processes, optimizing costs, increasing energy efficiency and reducing the negative impact on the environment.At the theoretical level, the study analyzes the key concepts and methodologies underlying the formation of energy security management strategies. Special attention is paid to theoretical approaches to risk forecasting, threat identification, and the integration of the latest technologies, such as artificial intelligence and automated monitoring systems, into the strategic planning process. Theoretical analysis helps to reveal the main principles and strategies that are critical for adapting to a rapidly changing external environment and new threats.At the practical level, the study considers real cases and examples of the implementation of energy security strategies at industrial enterprises. Analyzes of best practices, emergency planning, crisis recovery, and resource management are included. The issue of coordination between different levels of management and integration of the energy security strategy with other corporate plans and state regulatory requirements is considered separately.The study emphasizes the need to create adaptive management systems that not only ensure the reliability of energy supply, but also respond promptly to various threats, including natural disasters, man-made accidents, terrorist acts and cyber attacks. The practical aspect of the research also includes evaluating the effectiveness of monitoring and feedback systems for adapting strategies based on changes in the external environment and monitoring results.The conducted research makes a significant contribution to the scientific discussion on the strategy and planning of energy security management, combining theoretical foundations with practical recommendations. Scientifically based methods of forecasting threats and developing adaptive strategies ensure effective management of energy security of industrial enterprises in the context of modern global challenges and technological changes.
Keywords: management; energy security; risks; threats; monitoring; energy enterprise; efficiency; strategy; planning